DISPUTool 2.0: A Modular Architecture for Multi-Layer Argumentative Analysis of Political Debates - Goffredo, Pierpaolo; Cabrio, Elena; Villata, Serena; Haddadan, Shohreh; Torres Sanchez, Jhonatan (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Political debates are one of the most salient moments of an election campaign, where candidates are challenged to discuss the main contemporary and historical issues in a country. These debates represent a natural ground for argumentative analysis, which has always been employed to investigate political discourse structure and strategy in philosophy and linguistics. In this paper, we present DISPUTool 2.0, an automated tool which relies on Argument Mining methods to analyse the political debates from the US presidential campaigns to extract argument components (i.e., premise and claim) and relations (i.e., support and attack), and highlight fallacious arguments. DISPUTool 2.0 allows also for the automatic analysis of a piece of a debate proposed by the user to identify and classify the arguments contained in the text. A REST API is provided to exploit the tool’s functionalities.